Extraneural Metastasis of Primary Glioma Occurring in a Setting of Occupational Ionizing Radiation Exposure - Nitya Prabhakaran; Douglas C. Miller; N. Scott Litofsky; Shellaine R. Frazier (Case Reports in Neurological Medicine)
Malignant gliomas account for 60% of all primary brain tumors in adults. Glioblastoma Multiforme (GBM) is the most common primary glial tumor with a dismal prognosis and a median survival of approximately 14 months. Extra-neural metastases from primary brain tumors are unusual with an incidence rate of less than 2%. This has been attributed to factors such as short survival, lack of true lymphatics in the CNS, and physical barriers provided by the dura, extracellular matrix, and basement membrane. Although most GBMs occur sporadically, there is a known association with therapeutic radiation exposure and with work in nuclear disaster cleanup. To our knowledge, no case of GBM with metastasis occurring in a patient with occupational radiation exposure currently exists in the literature. In this article, we present a case of GBM with lung metastasis occurring in a 51-year-old Caucasian male, whose history is significant for occupational exposure to ionizing radiation, and review the literature on GBM risk factors and potential mechanisms of metastasis.